Does the "monitorial citizen" exist? : an empirical investigation into the occurrence of postmodern forms of citizenship in the Nordic countries - Hooghe, Marc; Dejaeghere, Yves (2007)
Contiene bibliografía
Keywords: Ciudadano; Europa septentrional